Impact of a brief educational intervention on eating habits in a sample of Peruvian adolescents aged 10–12 years: a preliminary study - Garcia-Castillo, Yasti; Elera-Campos, Ariana; Rodríguez-Vásquez, Mery; Javier-Aliaga, David (Frontiers in Public Health, 2025)
IntroductionCurrently, the prevalence of overweight and obesity among adolescents is a relevant public health concern. In this context, schools are considered a suitable setting for promoting healthy eating habits from an early age. Within this framework, the present study aimed to preliminarily explore the impact of a brief nutritional education intervention on eating habits in a sample of adolescents aged 10–12 years from a public school in Lima, Peru.Materials and methodsA quantitative study with a quasi-experimental design was conducted, including an experimental group (n = 16) and a control group (n = 8), under a pretest–posttest scheme. The final sample consisted of 24 adolescents aged 10–12 years, selected through simple random sampling. An eating habits questionnaire was administered before and after the educational intervention. The educational program lasted 2 months and comprised six sessions.ResultsThe brief nutritional program produced a significant improvement in the eating habits of the experimental group (p < 0.001), whereas the control group showed no changes (p = 0.495). In addition, both groups were equivalent at pretest (p = 0.928), but at posttest the experimental group exhibited a significant difference compared to the control group (p = 0.004), confirming the effectiveness of the intervention.ConclusionThe findings of this study provide preliminary evidence that brief educational interventions in school settings may contribute to the improvement of eating habits. These results support the relevance of considering nutritional education as a preventive strategy within public health policies to promote healthy lifestyles from early ages.